PKM Pelatihan Mengatasi Stres Akademik pada Siswa SMK - Lukman Lukman; Abdul Rahmat; Astiti Tenriawaru Ahmad; Amirah Aminanty Agussalim; Nurfajriyanti Rasyid (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2024)
Stressors for students at school can arise from situations that cause feelings of frustration, conflict, pressure, change, or self-imposed demands. Data obtained shows symptoms of stress in students, such as anxiety during exams, difficulty understanding material, and short deadlines for assignments. These stressful conditions trigger physical and emotional reactions that interfere with students' performance at school. The inability to implement effective coping strategies is one of the main causes of academic stress. Therefore, it is expected that the training provided can help reduce perceived academic stress. The problem-solving approach is carried out through training activities consisting of five stages: training needs analysis (TNA), material planning and module preparation, implementation, result measurement, and training evaluation. The implementation of these activities showed a decrease in the academic stress scores of students with moderate to high stress levels, both immediately after the training and 12 weeks later. However, this decrease was not statistically significant.